Distribution and sources of polycyclic aromatic hydrocarbons (PAHs) in surface sediments of a Tropical Bay influenced by anthropogenic activities (Todos os Santos Bay, BA, Brazil). (December 2018) - de Almeida, Marcos; do Nascimento, Danielle Vasconcelos; de Oliveira Mafalda, Paulo; Patire, Vinicius Faria; de Albergaria-Barbosa, Ana Cecília Rizzatti
Abstract: The present study aimed to evaluate the distribution and origin of 16 Priority PAHs in surficial sediment samples of Todos os Santos Bay (TSB, Brazil). Total PAHs concentrations ranged from below the method detection limit (<DL) to 533 ng g −1 (dry weight). The toxic equivalent concentrations (TEQ carc ) of PAHs in the studied area ranged from 0 to 104 ng g −1 and were lower when compared to other contaminated bays in the world. Diagnostic ratios indicated that pyrogenic processes, such as pyrolysis of fossil fuel, biomass, and coal, were the main PAHs sources for sediments. Proximity of the sources, the hydrodynamics and geochemistry of the sediments were the factor influencing the distribution of PAHs along the studied area. Highlights: The contamination levels of PAHs in Todos os Santos Bay were low to moderate. Areas closer the anthropic activities showed higher concentrations of PAHs. There are multiple sources of PAHs to the bay sediment. PAHs with 4–6 rings were dominant in the sediments of bay. TEQ carc indicated a good preservation of the bay, with low risk to biota.